2020
DOI: 10.1111/mec.15585
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterning of soil microbial communities created by fungus‐farming termites

Abstract: Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…Such colonies can live for decades but can create centuries-long legacies when their painstakingly-built mounds get recolonized after the founders' death 4 . Owing to termites' soil engineering and nutrient cycling, each mound has properties that differ from those of the between-mound matrix, such as different and more diverse microbial communities 5 , different and more productive plant communities 6 , higher abundance of insects and arthropods, or more frequent use by herbivores. But the emergent spatial patterning of the mounds has ecosystemwide consequences that could not be predicted from the properties of individual mounds, much less from those of individual termites.…”
Section: Corina Tarnita: Emerging Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such colonies can live for decades but can create centuries-long legacies when their painstakingly-built mounds get recolonized after the founders' death 4 . Owing to termites' soil engineering and nutrient cycling, each mound has properties that differ from those of the between-mound matrix, such as different and more diverse microbial communities 5 , different and more productive plant communities 6 , higher abundance of insects and arthropods, or more frequent use by herbivores. But the emergent spatial patterning of the mounds has ecosystemwide consequences that could not be predicted from the properties of individual mounds, much less from those of individual termites.…”
Section: Corina Tarnita: Emerging Patternsmentioning
confidence: 99%
“…But the emergent spatial patterning of the mounds has ecosystemwide consequences that could not be predicted from the properties of individual mounds, much less from those of individual termites. The thousands of hexagonally distributed mounds altogether boost microbial diversity and ecosystem productivity more than if the same mounds had been randomly scattered 5,6 , and they are predicted to substantially enhance ecosystem robustness to climatic perturbations 2 .…”
Section: Corina Tarnita: Emerging Patternsmentioning
confidence: 99%
“…We assessed habitat selection relative to three factors: distance to nearest termite mound, woody cover, and lion utilization. We used a continuous metric of mound proximity in lieu of a categorical on/off mound variable to reduce bias from GPS error and also because the effects of termite mounds on soils and plants typically extend well into the matrix (Baker et al, 2020; Pringle et al, 2010; Sileshi et al, 2010) such that herbivores may use mound‐associated resources even when not on a mound (although the spatial extent of this effect in our system is unknown). We included the latter two covariates to help control for residual variation in selection for termite mounds, given the known effects of tree cover on real/perceived predation risk and antelope behavior (Atkins et al, 2019; Ford et al, 2014; le Roux et al, 2018; Tambling et al, 2013; Valeix et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Termitaria supported distinct assemblages of nutrient-rich plant species, and all antelope species selected for mound-associated space and food. Strong effects of fungus-farming termites on plant species composition, productivity, and nutrient content-arising from alteration of soil structure, chemistry, and moisture-appear to be nearly universal in African savannas and tend to decay nonlinearly with distance from mound centers (Baker et al, 2020;Joseph et al, 2013;Moe et al, 2009;Pringle et al, 2010;Seymour et al, 2014;Sileshi et al, 2010;Sileshi & Arshad, 2012). Many studies have also found that mound-associated plants are heavily used and affected by herbivores (Grant & Scholes, 2006;Holdo & McDowell, 2004;Joseph et al, 2018;Levick et al, 2010;Loveridge & Moe, 2004;Mobaek et al, 2005;Okullo et al, 2013;Seymour et al, 2016), but this effect is not universal and several studies have reported the opposite pattern (Davies, Levick, et al, 2016;Muvengwi et al, 2013Muvengwi et al, , 2019O'Connor, 2013;Van der Plas et al, 2013).…”
Section: Termite Mounds As Resource Hotspots For Large Herbivores (Hy...mentioning
confidence: 99%
“…At the same site, Pringle et al. (2010) observed that mounds built by Odontotermes species improved plant productivity while Baker et al. (2020) reported that Odontotermes montanus affected the diversity of fungi and bacteria at localized points within mounds.…”
Section: Introductionmentioning
confidence: 99%